Platelets in thrombotic and non-thrombotic disorders : pathophysiology, pharmacology and therapeutics : an update - Gresele, Paolo, 1953-; Kleiman, Neal S.; Lopez, José A.; Page, C. P. (Springer, 2017)
This book reviews current science and applications in fields including thrombosis and hemostasis, signal transduction, and non-thrombotic conditions such as inflammation, allergy and tumor metastasis. It is a detailed, up-to-date, highly referenced text for clinical scientists and physicians, including recent developments in this rapidly expanding field. More than a scientific resource, this is also an authoritative reference and guide to the diagnosis.- Resumé vydavatel
Keywords: trombocyty; histopatologie; thrombocytes; histopathology; elektronické knihy; sborníky; electronic books; papers of several authors